Pemberian Hak Eksklusif Oleh Negara Kepada Pemilik Merek Terdaftar Untuk Jenis Barang Dan Jasa Dalam Konsep Konsitutif Asas First To File - Solihin, Henky; Budiana, Budiana; Rahman, Budi; Nurhayati, Rika; Bakar, Bakar (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This study examines the granting of exclusive rights by the state to registered trademark holders based on the constitutive principle and the first to file approach. Legal protection for trademarks in Indonesia is only granted if the owner registers it formally, not merely based on prior use. The aim of this study is to analyze the effectiveness of the first to file principle within the constitutive framework and its implications for legal certainty. This research employs a normative juridical method with a doctrinal approach. Secondary data—including primary, secondary, and tertiary legal materials—was collected through library research and analyzed qualitatively using deductive reasoning. The study focuses on the trademark registration mechanism at the Directorate General of Intellectual Property. The findings reveal that trademark registration in Indonesia involves formal examination, public announcement, and substantive examination as procedural steps to obtain lawful protection. This system ensures legal protection for good-faith applicants and prevents ownership conflicts. The study concludes that the application of the first to file principle within a constitutive legal framework offers legitimate and effective protection for trademark rights, serving as a vital legal tool to uphold certainty within Indonesia’s intellectual property system.